A South African perspective on professional ballet dancers' career transitions (2018 - 2021) - Dean, Amy Denise (School of Dance, 2023)
The discourse of dancers' and career transitions has significantly increased since the 1980s, and much of the literature views the topic of dancers and career transitions from European, American and Australian perspectives. No literature from a South African perspective was found, and this research dissertation aims to fill this gap. This research explores the phenomenon of a dancer's career transition from a South African perspective through a microcosm - four interviews conducted with former professional ballet dancers from a single ballet company. The aim was to answer the main research question; What is the experience of South African ballet dancers transitioning from a full-time professional stage performing career to alternative careers or roles? A Phenomenological case study was applied to explore and identify the former dancer's transition experiences. Qualitative data was gathered through in-depth interviews with four former dancers who had been employed full-time by a single company in the Western Cape, South Africa. The transcripts of the data collected were analysed using thematic analysis, and four themes emerged: 1. Loss, grief and coping processes. 2. Preparation for an exit. 3. Support systems. 4. South African experience versus outside South Africa experience. Several established theories and models were used to underpin the interpretations and understandings of the experiences of these former dancers. These include Irina Roncaglia's Career Transition Model for Ballet Dancers (Roncaglia, 2006), Colin Murray Parkes' Psychosocial Transition Theory (1998), Margret Stroebe and Henk Schut's Dual-process Model of Coping and Bereavement (1995), Britton Brewer, Judy Van Raalte and Darwyn Linder's Athletic Identity (1993), and Carolyn Cutrona and Daniel Russell's ideas on types of Social Support (1990) along with an exploration on the profile of South African dancers. The research demonstrates that even though South African ballet dancers find themselves in different training and performing environments compared to their European, American and Australian counterparts, the experiences of dancers' transitioning out of a professional stage performing career have similar themes yet are unique for each individual. The research also comments on suggestions to improve South African dancers' experiences while considering the socio-economic climate of Dance in South Africa. Recommendations for further study are made, borne from the limitations and findings of this research. In closing, although zoomed into experiences from a single ballet company, the four themes provide an answer to the research question, which allows for a new perspective (South African) to be added to the already established dialogue of dancers and career transitions.